Avaliação das metodologias do estudo de vazão máxima provável: estudo de caso da Bacia Hidrográfica do Rio Ji-Paraná/RO - Mercadante, Olivia de Castro (2018)
Defining metrics when designing maximum flow has always been questioned due to the quality and quantity of the available data. Most designs consider the project flow in relation to the exceptional probability within a set time, with a direct correlation to the associated risk. This thesis displays an evaluation of the different methodologies to determine maximum probable flood, whilst taking in consideration statistical and hydrometerological methods, in accordance to the recommendations of the WMO. In order to quantify and compare the various methods, a case study will be presented for the Ji-Paraná watershed. Lastly, it is concluded that the hydrometereological approach represents an advancement over the currently used techniques, since it is consistent with physical phenomena and allow the assignment of probabilities to hydrological variables, ultimately resulting in more realistic project values.